Successful Treatment of Plasma Cell-Rich Acute Rejection Using Bortezomib: A Case Report - Sara Hashemi; Reut Hod-Dvorai; Rebecca Tong; Liye Suo (Case Reports in Transplantation)
Plasma cell-rich acute rejection (PCAR), a relatively rare subtype of acute allograft rejection, is usually associated with a significantly lower treatment response rate and a higher graft failure rate. PCAR is characterized by the presence of more than 10% of plasma cells out of all graft infiltrating cells, with approximately 40%–60% of PCAR resulting in graft failure within a year. Currently, there is no gold standard for the effective treatment of PCAR. This case report demonstrates the potential treatment effect of bortezomib in PCAR. A 37-year-old woman with reflux nephropathy received a kidney transplant from a brain-dead kidney donor. The patient presented with an acute kidney injury with a serum creatinine level over 4 mg/dL 4 months after the surgery. The allograft biopsy showed acute T cell–mediated rejection (TCMR), Grade IIA, plasma cell-rich variant. There were diffuse polyclonal plasma cells infiltrating the renal parenchyma with marked tubulitis and focal endarteritis. She received a methylprednisolone pulse of 500 mg daily x3, followed by thymoglobulin (rATG) at 4.2 mg/kg. However, a repeated biopsy after 2 months showed persistent plasma cells infiltrate with increased interstitial fibrosis with tubular atrophy. Then, the patient was given one cycle of bortezomib with a total of four subcutaneous injections and continued immunosuppressants of tacrolimus, mycophenolate mofetil, and prednisone. Following the treatment, the patient’s serum creatinine level trended down to 2 mg/dL, and a second repeat biopsy after 4 months showed a significant treatment effect with complete resolution of interstitial inflammation and decreased chronicity. Bortezomib is a proteasome inhibitor that prevents cell proliferation by inducing apoptosis in plasma cells and has shown great promise as a therapeutic agent for multiple myeloma. Our case suggests that bortezomib can also be used as a potential therapeutic intervention for patients with PCAR.